Why did ancient states collapse? : the dysfunctional state - Levitt, Malcolm, (Access archaeology., 2019)
Rooted in agriculture, sedentism and population growth, ancient states were fragile and prone to collapse. There is an ongoing debate about the importance, nature and even existence of state-wide collapse. This book investigates why ancient states collapsed and examines to what extent inequality contributed to their downfall.